A case series of young women with spontaneous regression of vulval intraepithelial neoplasia: Demographics and associated HPV genotypes. (4th March 2016) - Hilton, Jackie; Perkins, Nicky; Tabrizi, Sepehr N.; Jones, Ronald W.
Abstract : Objective: To review the clinical features, demography and human papillomavirus (HPV) genotype in a group of young women with usual type vulval intraepithelial neoplasia (VIN) whose lesions regressed spontaneously. Materials and Methods: A retrospective case note review was made of the records of women with a diagnosis of usual type VIN whose lesions resolved spontaneously. The clinical features, demography, associated conditions, time to regression and follow‐up data were extracted. Stored paraffin‐embedded biopsy tissue was tested for the presence and genotype of HPV. Results: Fifty‐four women were identified. The median age at diagnosis was 19 years. Forty‐four women (81%) were of non‐European ethnicity. The median time to regression was 9 months. In 44 (81%) cases, the lesion was an incidental finding during clinical examination. The majority of lesions were multifocal and pigmented (44 (81%) and 48 (89%), respectively). HPV was detected in 40 (87%) of the 46 available biopsy samples, and HPV genotype 16 was identified in 33 (82.5%). Recurrences of usual type VIN occurred in three women, and these all resolved spontaneously. Conclusion: Women diagnosed with usual type VIN which resolves spontaneously are very young, mainly non‐European, and usually present with multiple, asymptomatic pigmented lesions. HPV genotypes and their frequencies are similar to those detected in older women with usual type VIN. This clinically defined group of women may be managed by observation alone if follow‐up is assured.